Urbanization Impacts on Pearl River Delta Extreme Rainfall Sensitivity to Land Cover Change Versus Anthropogenic Heat. Issue 3 (11th March 2021) - Hu, Chenxi; Fung, Kwun Yip; Tam, Chi‐Yung; Wang, Ziqian
Abstract: Impacts of urban land cover and anthropogenic heat (AH) on extreme local rainfall over the coastal Pearl River Delta (PRD) megacity region during boreal summer are investigated by conducting numerical experiments using the Weather Research and Forecastingmodel coupled with a single‐layer urban canopy model. To examine the relative importance of land cover change versus the presence of AH, three numerical experiments corresponding to different levels of urbanization in the PRD area were designed: one with cropland covering the whole region, one with urban land cover but zero AH, and one with urban land cover and a strong diurnal maximum of 300 Wm −2 of AH in the model simulations. Results show that the increase of rainfall in the urban area is much more sensitive to the intensity of AH than the mere change of surface properties. Urbanization with intense AH can enhance both the intensity and frequency of extreme rainfall, which can be attributed to higher surface temperature (of about 3.5–4°C), higher convective available potential energy, and lower convective inhibition, thus creating an environment more conducive to strong convection over the urban areas. Moreover, enhanced rainfall is supported by moisture supply from the South China Sea and increased water vapor flux convergence over the PRD city area. The amount of moisture flux converging over the coastal megacity area was found to depend on the direction of prevailing background wind. Key Points: Extreme rainfall is sensitive to the extent of urbanization in the Pearl River Delta area, in which anthropogenic heat play a crucial role Higher CAPE, lower CIN, and more moisture flux convergence due to urban heat island effect can lead to stronger extreme rainfall Though urbanization reduces surface evaporation, moisture supply from the ocean can still support the intensification of extreme rainfall